Mercado laboral y su influencia en la inserción de las/os secretarias/os del cantón Vinces - Bobadilla Vera, Limbert Roly (2022)
The present work was based on the objective of determining what is the influence of the labor market in the insertion of the secretaries in the Civil Protection Institution of the Vinces Canton. The present case study was carried out through the application of field research, the quantitative method and a survey was also implemented as an instrument for collecting information, which helped to understand the problem and to draw relevant conclusions in the investigation. In addition, the theoretical supports served for a better understanding of the problematic situation. With the information obtained in the current case study, it revealed the gaps related to the problem and suggested possible solutions related to them, for self-knowledge and self-assessment.